Optimizing Muara Coffee and Space Digital Marketing Strategy Using Instagram - Abidzar Syehabuddin; Dewi Pungkawati; Entri Melyani Sahara (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study is to research and analyze how the strategy is to optimize the digital marketing strategy of Muara Coffee and Space using Instagram to support increasing the marketing results of an MSME. Considering that we have entered the digital era where the use of social media is being widely used, the marketing strategy through Instagram is very important because through Instagram marketing strategies can be packaged in the most attractive way possible to attract the interest of consumers. can see direct feedback from consumers besides that Instagram is also a platform that is currently widely used by the community so this research will produce ways to optimize Instagram as a digital marketing medium for a business. This research uses descriptive analysis studies with qualitative research methods. The things discussed in this study are (1) Instagram in networked consumers, (2) Interaction in social media, (3) Marketing strategy using Instagram. From what will be discussed, this research will result in how to optimize social media as a digital marketing strategy to increase consumer interest.